Hybrid Corn Agribusiness Development Strategy in Deli Serdang Regency - Handayani, Leni; Sitompul, Ralando; Adetrya, Dirga; Maratawan, Guru; Dedi, Ahmad; Iyusnizar, Iyusnizar; Ghania, Miftahul; Wahyudi, Denny; Sari, Masita; Ridwan, Muhammad; Adellini, Marcellina; Jun, Samuel; Tampubolon, Lukman; Sudarmaji, Sudarmaji; Kurniawan, Diki (Westscience Press, 2025)
This study finds the implications of the hybrid corn agribusiness development strategy and provides recommendations for strategies and policies for developing hybrid corn agribusiness in Deli Serdang Regency. This research is crucial for the future development of hybrid corn agribusiness. It employed a quantitative descriptive method. Qualitative research generally employs three design models: descriptive, verification, and grounded research. The research subjects were 60 hybrid corn farmers. The research focused on strategies for developing hybrid corn agribusiness and provided recommendations for strategies and policies for developing hybrid corn agribusiness. This research was conducted in Deli Serdang Regency, specifically in the districts of Tanjung Morawa, Lubuk Pakam, Beringin, and Namorambe. The results suggest that utilizing government support and farmer groups (gapoktan) to obtain quality seeds and utilizing average input prices and input availability can increase hybrid corn production. The hybrid corn agribusiness development strategy shows a value of x> 0, namely 1.67 and a value of y> 0, namely 1.41. This means that the position of the hybrid corn agribusiness development strategy is located in quadrant I. Quadrant I is a quadrant that is bounded by the x-axis and y-axis, both of which are positive and the recommended alternative strategy is an aggressive strategy, namely the SO strategy (Strategy - Opportunity), where this quadrant has the most profitable position because the strengths and opportunities in the position matrix are good so that with the strengths that farmers have in their farming, it is possible to take advantage of existing farming opportunities and develop them.